PENGGUNAAN MINYAK NYAMPLUNG SEBAGAI BAHAN BAKAR ALTERNATIF PENGGANTI MINYAK TANAH - Jimmy, Jimmy (Jurnal Teknik Kimia, 2012)
Vegetable oil have a higher flash point compared with kerosene. Because of the higher flash point, it would require an effort to lower the flash point. This study aimed to determine the effect of the composition ratio of ethanol and ethyl lactate in lowering nyamplung oil flash point. To determine the ratio of ethanol and ethyl lactate, preliminary experiments carried out by the addition of additives in the ratio 1:1; 1:2; 1:3; 2:1; 2:3 on nyamplung oil for determining the solubility of additives in the nyamplung oil. The result gives good  solubility for ratio 1:1. Concentrations of ethanol additive used each are 0%, 1%, 2%, 3%, 4%, 5%. Nyamplung oil used as much as 200 grams. Additives mixing made in stirred vessel at room temperature with slow stirring for 10 minutes. It can be concluded that the addition of ethanol and ethyl lactate additive effect on the decline in oil flashpoint nyamplung, nyamplung oil with ethanol and ethyl lactate concentration of each of the 2% obtained by the flash point 550C, density 0.9358 g/cm3 and viscosity 43.71 mm2/s. Nyamplung oil with additive ethanol and ethyl lactate more appropriately applied to the press stove. Keywords: composition of ethanol and ethyl lactate, flash point, nyamplung oil